Answer:
D .8
Step-by-step explanation:
hypotenuse (h) = 10
base (b) = 6
perpendicular (p) = a= ?
We know by using Pythagoras theorem we get
p = √ h² - b²
a = √ 10² - 6²
a = √ 64
a = 8
Hope it will help :)
Answer:
and let's then do away with the denominators, by multiplying both sides by the LCD of all fractions, in this case, the LCD will be 8, and then we'll combine the like-terms, but anyway, let's proceed.
Step-by-step explanation:
Answer:
answer becit uses b
Step-by-step explanation:
but yass queen but annyway
Answer:
Step-by-step explanation:
32
The value of the given expression (3m - n)² + 4m when m = 63 and n = 45 is equal to 20,916.
<h3>What is an expression?</h3>
An expression can be defined as a mathematical equation which is used to show the relationship existing between two or more variables and numerical quantities.
<u>Given the following variables:</u>
Substituting the given variables into the given expression, we have;
Expression = (3m - n)² + 4m.
Expression = (3(63) - 45)² + 4(45).
Expression = (189 - 45)² + 180
Expression = 144² + 180
Expression = 20,736 + 180
Expression = 20,916.
Read more on expressions here: brainly.com/question/28260012
#SPJ1
Complete Question:
Evaluate the expression when m = 63 and n = 45. (3m - n)² + 4m.